In vitro Evaluation of the Anti-inflammatory Effects of Thymoquinone in Osteoarthritis and in silico Analysis of Inter-Related Pathways in Age-Related Degenerative Diseases - Kalamegam, Gauthaman; Alfakeeh, Saadiah M.; Bahmaid, Afnan Omar; AlHuwait, Etimad A.; Gari, Mamdouh A.; Abbas, Mohammed M.; Ahmed, Farid; Abu-Elmagd, Muhammed; Pushparaj, Peter Natesan (Frontiers in Cell and Developmental Biology, 2020)
Chronic inflammation is a common underlying factor in osteoarthritis (OA) and most age-related degenerative diseases. As conventional therapies help only in partial alleviation of symptoms in OA, stem cell-based therapies and herbal supplements are being widely explored. Thymoquinone (TQ), an active ingredient of Nigella Sativa is reported to have immunomodulatory, anti-inflammatory and antioxidant properties. We evaluated the effects of TQ on bone marrow MSCs (BM-MSCs) derived from OA patients and its interrelated pathways in inflammation and age-related degenerative diseases using Ingenuity Pathway Analysis (IPA) as well as possible molecular targets using SwissTargetPrediction. BM-MSCs were derived from OA patients and their stemness properties were characterized by studying the MSCs related CD surface marker expression and differentiation into adipocytes, osteoblasts, and chondrocytes. Treatment with TQ (100nM - 5µM) demonstrated cell death, especially at higher concentrations. MTT assay demonstrated a significant concentration-dependent decrease in cell viability which ranged from 20.04% to 69.76% with higher doses (300nM, 1µM, and 5µM), especially at 48h and 72h. Additional cell viability testing with CellTiter-Blue also demonstrated a significant concentration-dependent decrease in cell viability which ranged from 27.80% to 73.67% with higher doses (300nM, 1µM, 3µM, and 5µM). Gene expression analysis following treatment of BM-MSCs with TQ (1µM and 3µM) for 48h showed upregulation of the anti-inflammatory genes IL-4 and IL-10. In contrast, the pro-inflammatory genes namely IFN-γ, TNF-α, COX-2, IL-6, IL-8, IL-16, and IL-12A although were upregulated, compared to the lower concentration of TQ (1µM) they were all decreased at 3µM. The pro-apoptotic BAX gene was downregulated while the SURVIVIN gene was upregulated. IPA of the molecular interaction of TQ in inflammation and age-related degenerative diseases identified canonical pathways directly related to synaptogenesis, neuroinflammation, TGF-β, and interleukin signaling. Further screening led to the identification of 36 molecules that are involved in apoptosis, cell cycle regulation, cytokines, chemokines, and growth factors. SwissTargetPrediction of TQ identified potential molecular targets with high probability. TQ exerted anti-inflammatory effects and therefore can be a useful adjuvant along with conventional therapies against inflammation in OA and other age-related degenerative diseases.